Menjelajahi Faktor Penentu Keuangan Dan Non-Keuangan Dalam Opini Audit Kelangsungan Usaha Di Sektor Barang Konsumsi - Rudiyanto, Rudiyanto; Herlina, Herlina; Saleh, M. Firdaus (Jurnal Bisnis, Manajemen dan Akuntansi, 2025)
This article explores the analysis of the acceptance of audit opinion on going concern (OAGC) based on financial and non-financial factors. The factors studied include liquidity, solvency, profitability, and reputation of the accounting firm from 30 primary consumer goods industry companies. Our conclusions are based on logistic regression analysis of 150 observation data from 2019-2023. We obtain empirical evidence that OAGC is not formed from high or low liquidity (ROA) or solvency. However, it is significantly formed based on financial factors (profitability) and non-financial factors (auditors' reputation). This finding supports agency theory, which emphasizes the importance of transparency, accountability, and supervision to minimize conflicts of interest. The implications of this study highlight the importance of companies in increasing profitability and working with quality auditors. This finding can provide a strategic concept for management in decision-making and improve audit practices in the future.